Hydroponics for the home - Peréz E., Laura (IICA, 2021)
The book was designed as a manual, with practical advice and useful tips for beginners in this form of hydroponics agriculture, it presents in a more simple and practical way how to produce food in a small space inside the house, to experience the satisfaction of producing and harvesting a wide variety of chemical-free vegetables and other plants.